Overlapping and divergent signaling pathways of N-cadherin and VE-cadherin in endothelial cells - Giampietro, Costanza; Taddei, Andrea; Corada, Monica; Sarra-Ferraris, Gian Maria; Alcalay, Myriam; Cavallaro, Ugo; Orsenigo, Fabrizio; Lampugnani, Maria Grazia; Dejana, Elisabetta (Blood, 2012)
Endothelial cells (ECs) express 2 members of the cadherin family, VE and N-cadherin. Although VE-cadherin induces EC homotypic adhesion, N-cadherin function in ECs remains largely unknown. EC-specific inactivation of either VE or N-cadherin leads to early fetal lethality suggesting that these cadherins play a nonredundant role in vascular development. We report here that VE-cadherin negatively controls junctional localization and expression of N-cadherin by limiting p120-catenin availability and reducing β-catenin transcriptional activity. Using EC lines expressing either VE or N-cadherin we found that both cadherins inhibit cell proliferation and apoptosis. Both trigger the phosphatidylinositol-3-OH-kinase (PI3K)–AKT-Forkhead-box protein-O1 (FoxO1) pathway and reduce β-catenin transcriptional activity. The extent of signaling correlates with the total level of cadherins regardless of the type of cadherin expressed. In contrast, basal and fibroblast growth factor (FGF)–induced cell motility is promoted by N-cadherin and strongly inhibited by VE-cadherin. This opposite effect is partly because of the ability of VE-cadherin to associate with FGF receptor and the density-enhanced phosphatase-1 (Dep-1) which, in turn, inhibits receptor signaling. We conclude that VE and N-cadherin have both additive and divergent effects on ECs. Differences in signaling are due, in part, to cadherin association with growth factor receptors and modulation of their downstream signaling.